Second Hankel determinant problem for a certain subclass of univalent functions - Yavuz, Tuğba (Hikari Ltd. hikaripublishers@m-hikari.com HIKARI LTD, P.O. Box 15 Ruse 7005, 2015)
Let S denote the class of analytic and univalent functions in the open unit disk D = {z : |z| < 1} with the normalization conditions. In the present artical an upper bound for the second Hankel determinant |a2a4 - a23| is obtained for a certain subclass of univalent functions. © 2015 Elsevier B.V., All rights reserved.
Keywords: Second hankel determinant; Univalent functions